2014
DOI: 10.1186/1471-2369-15-116
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell (RBC) transfusion rates among US chronic dialysis patients during changes to Medicare end-stage renal disease (ESRD) reimbursement systems and erythropoiesis stimulating agent (ESA) labels

Abstract: BackgroundSeveral major ESRD-related regulatory and reimbursement changes were introduced in the United States in 2011. In several large, national datasets, these changes have been associated with decreases in erythropoiesis stimulating agent (ESA) utilization and hemoglobin concentrations in the ESRD population, as well as an increase in the use of red blood cell (RBC) transfusions in this population. Our objective was to examine the use of RBC transfusion before and after the regulatory and reimbursement cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…One key finding concerned the relationship between hemoglobin variability and use of red blood cell transfusions. While other studies have demonstrated increasing use of transfusions in recent years [ 34 , 35 , 36 ], the present report provides additional detail. Transfusions increased most strikingly in the LL group, suggesting that transfusions have become a more important treatment option in patients with persistently low hemoglobin levels.…”
Section: Discussionmentioning
confidence: 77%
“…One key finding concerned the relationship between hemoglobin variability and use of red blood cell transfusions. While other studies have demonstrated increasing use of transfusions in recent years [ 34 , 35 , 36 ], the present report provides additional detail. Transfusions increased most strikingly in the LL group, suggesting that transfusions have become a more important treatment option in patients with persistently low hemoglobin levels.…”
Section: Discussionmentioning
confidence: 77%
“…This retrospective observational cohort study used (i) Truven Health MarketScan ® Commercial Claims and the Medicare Supplemental database and (ii) the Oncology Services Comprehensive Electronic Records (OSCER) database, which includes information on cancer patients from US outpatient community and hospital‐affiliated oncology practices . Both databases are fully compliant with the Health Portability and Accountability Act of 1996, and all data were deidentified to protect the privacy of patients and providers.…”
Section: Methodsmentioning
confidence: 99%
“…Our primary definition of chronic dialysis dependence was at least one occurrence of BETOS 9A or 9B during the 12 months before the index fistula/graft month or within 30 days after creation of the index fistula/graft (8). A sensitivity analysis defined dialysis dependence by occurrence of BE-TOS 9A or 9B in 3 consecutive months, with the third month being no later than 2 months after the index fistula/graft month (9).…”
Section: Methodsmentioning
confidence: 99%